Grammatical change in Paris French: in situ question words in embedded contexts. Issue 2 (31st July 2018) - GARDNER-CHLOROS, PENELOPE; SECOVA, MARIA
ABSTRACT: This article will review the parameters of a grammatical variable within the putative variety 'Multicultural Paris French', i.e. its distribution and use within a group of young banlieue speakers. The structure in question stands out as it has rarely been found in previous corpora in France: indirect questions following verbs like savoir, where the question word is post-verb ( je sais pas il a dit quoi ). We discuss which groups use the new forms in Paris, referring briefly to some comparable changes in London. This structure appears to be an instance of 'change from below' (Labov, 2007), which seems to have emerged in the speech of young people of immigrant background. It might also, on the other hand, be a long-standing vernacular variant, which has re-emerged, with specific identity-related significance, in this particular group of speakers. Its exceptional character in the Paris context highlights a lack of evidence for the emergence of a more wide-ranging, distinct multiethnolect, as found in London and other European capitals.